(untitled) (Archives of Mechanics - Test, 2000)
Solution of the generalized plane deformation problem of a piezoelectric material strip with a crack is proposed. Laplace and Fourier transforms are used to reduce the problem to the solution of singular integral equations in the Laplace transform plane. Laplace inversion yields the results in the time domain. This analysis yields six independent stress and three electric displacement components. The model is general enough to account for arbitrary polarization direction, under transient or steady state load, for any mechanical or electrical mode of cracking. Numerical solutions for a piezoelectric material strip under electromechanical impact are illustrated. The influences of strip thickness and crack position on time-dependent crack tip fields are investigated. The results show that the transient electric displacement loads can increase or reduce the stress intensity factors at different time, dependent on the applied electric displacement load direction.